The struggle for civil society in Central Asia : crisis and transformation - Buxton, Charles, 1951- (Sterling, VA : Kumarian Press, 2011)
"After the collapse of the Soviet Union, NGOs and civil society (CS) actors in Central Asia found themselves struggling to set up new organizations that would fight for democracy, sustainable development and social justice. It was a time of great hopes, disappointments and interrupted progress for a region largely neglected by the powerful global actors.
The Struggle for Civil Society in Central Asiadescribes the gradual establishment of the CS sector in Central Asia despite the economic and social crises that marked the first decade of independence in the region. It shows how the neo-liberal policies of international agencies failed to spur progress in the 1990s and how national government control gradually re-asserted itself after 2000. The book also covers the effects of 9/11 on CS, the impact of 'colored revolutions' and the challenges that civil society organizations face today."--pub. desc.
Part One - Independence -- 1) The 1990s: The Formation of Civil Society as Society Collapses -- 2) Ideologies of Civil Society: What Does it Actually Mean? -- 3) Cleaning up the Damage: NGOs and Environmental Hot-Spots -- Part Two -- The Present -- 4) NGO-State Relations: Civil Society in Kyrgyzstan's Tulip Revolution -- 5) The Women's Movement Between East and West -- 6) Civil Society Networks: From Local to Regional in Central Asia -- Part Three -- The Future -- 7) Civil Society Within the Emerging Political Economy of Central Asia -- 8) Linking to Global Debates: How CSOs are Finding their Voice and What They Are Saying
Includes bibliographical references and index.
Keywords: Civil society -- Asia, Central; Asia, Central -- Politics and government -- 1991-